How Does an Engineer Use Science? - Owen, Ruth, 1967-; Wood, Alix; Sachner, Mark J. ([Tunbridge Wells, Kent] : Ruby Tuesday Books Ltd., 2024)
Exploring the science behind the jobs! Young readers can discover h ow science is used by Engineers every day in their jobs.
Keywords: Engineers -- Juvenile literature; Science -- Juvenile literature